Hubungan Kemudahan Pemenuhan Persyaratan, Prosedur, danAplikasi Kajian Direktorat Standardisasi Pangan Olahan BPOMdengan Kepuasan Pelanggan - Sari Indira Setyowati; Sentani Chasfila (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
To meet the publics’ needs for the safety and quality of processed food, the Directorate of Processed Food Standardization provides public services for assessing safety, quality, nutrition, benefits, and labeling; the safety of genetically modified organism (GMO) products; and approving clinical tests. The public service quality achievement can be measured using a Public Satisfaction Survey among stakeholders, in the form of an index that explains the expectations and performance of public services received by customers. This research was conducted to determine the variables related to customer satisfaction regarding assessment service completion time, assessed through the ease of fulfilling requirements, the ease of service procedures, and the availability of supporting applications.The research method used is quantitative, with a cross-sectional design. The data used comes from the Public Satisfaction Survey (SKM) of business actors who received assessment services in 2023 and 2024. The research was based on the perceptions of 41 respondents, comprising 9 males (22%) and 32 females (78%). The research results show that ease of service, procedural requirements, and application availability are related to customer satisfaction with the time to complete the assessment service (sig. < 0.05).To improve services, several steps can be considered, such as improving the stability of the system infrastructure, improving the existing requirements, procedures, and systems. Conduct outreach, technical guidance, and coaching clinics for applicants. Furthermore, it is necessary to improve the technical competence of evaluators in order to reformulate and simplify the documents needed.